Fall Harvest Management of Eastern Gamagrass in Central Wisconsin. Issue 1 (1st December 2014) - Coblentz, Wayne K.; Bertram, Michael G.; Hoffman, Patrick C.; Esser, Nancy M.; Cavadini, Jason S.
Abstract : Research has suggested that eastern gamagrass (EGG) may be an effective alternative to chopped straw in the blended diets of dairy heifers and cows. Extension materials discussing appropriate fall management of EGG often recommend avoiding harvest within 6 weeks of first frost. However, previous research has shown that single‐harvest dry‐matter (DM) yields are not maximal by mid‐August in central Wisconsin; most probably this occurs because of inadequate accumulation of growing degree days by that date. Our objectives were to evaluate DM yield, plant persistence, and nutritive value for EGG harvested at 15‐day intervals between 1 August and 1 November. Yields of DM (2010 through 2013) increased with linear ( P = 0.001) and quadratic ( P < 0.001) effects across harvest dates, peaking at >6600 lb/acre (7392 kg/ha) on 15 September and 1 October. Overall DM yields varied with year but were greatest ( P ≤ 0.001) during the final year (2013) of the trial (7099 lb/acre; 7951 kg/ha). The percentage of continuous row coverage also was assessed but was not affected by harvest date ( P ≥ 0.218). In central Wisconsin, single‐cut harvests of EGG timed as late as 1 October improved DM yields relative to August harvest dates without compromising plant persistence.